2015
DOI: 10.1186/s13024-015-0064-1
|View full text |Cite
|
Sign up to set email alerts
|

Tau missorting and spastin-induced microtubule disruption in neurodegeneration: Alzheimer Disease and Hereditary Spastic Paraplegia

Abstract: In Alzheimer Disease (AD), the mechanistic connection of the two major pathological hallmarks, namely deposition of Amyloid-beta (Aβ) in the form of extracellular plaques, and the pathological changes of the intracellular protein Tau (such as phosphorylation, missorting, aggregation), is not well understood. Genetic evidence from AD and Down Syndrome (Trisomy 21), and animal models thereof, suggests that aberrant production of Aβ is upstream of Tau aggregation, but also points to Tau as a critical effector in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 86 publications
1
67
0
Order By: Relevance
“…Notably, the amount of tau needed for in vitro LLPS induced with the neutral molecule PEG likely differs from the tau concentration critical for LLPS in a neuron, because (i) the intraneuronal distribution of tau is highly heterogeneous (usually high in the axon and low in the soma and dendrites), (ii) different isoforms and post‐translational modified and truncated forms of tau coexist, (iii) the pool of free soluble tau released from microtubules is highly dynamic depending on phosphorylation, and (iv) multiple other binding partners of tau have been identified that could deplete tau from the free soluble pool available for LLPS. Recently, it has also been shown that the usual distribution of tau in neurons can be changed upon exposure to A‐beta, which can induce the local transcription of tau in dendrites as well (Zempel & Mandelkow, 2015; Li & Götz, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Notably, the amount of tau needed for in vitro LLPS induced with the neutral molecule PEG likely differs from the tau concentration critical for LLPS in a neuron, because (i) the intraneuronal distribution of tau is highly heterogeneous (usually high in the axon and low in the soma and dendrites), (ii) different isoforms and post‐translational modified and truncated forms of tau coexist, (iii) the pool of free soluble tau released from microtubules is highly dynamic depending on phosphorylation, and (iv) multiple other binding partners of tau have been identified that could deplete tau from the free soluble pool available for LLPS. Recently, it has also been shown that the usual distribution of tau in neurons can be changed upon exposure to A‐beta, which can induce the local transcription of tau in dendrites as well (Zempel & Mandelkow, 2015; Li & Götz, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…However, a recent report suggested that pathological loss of dendritic spines and synapse activity may be caused by mislocalization of TTLL6 (and possibly of TTLL1, 5, or 11), leading to abnormal glutamylation patterns and excessive spastin-mediated severing of dendritic MTs [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Two major pathological hallmarks in AD are extracellular amyloid plaques and intraneuronal neurofibrillary tangle (NFT; Zhang et al, 2011). NFTs are comprised of hyperphosphorylated microtubule-associated protein tau (Song et al, 2015; Yamada et al, 2015; Zempel and Mandelkow, 2015). Amyloid plaques are primarily comprised of Aβ which is derived from sequential cleavages of APP by β- and γ-secretases (Zhang et al, 2011; Audrain et al, 2016).…”
Section: Abnormal Protein Aggregation In Neurodegenerative Diseasesmentioning
confidence: 99%